Development of an Arduino-Based Automated Irrigation System for Sandy Soil in Igbesa, Ogun State (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Agriculture relies on effective irrigation for crops to grow, especially in areas like Igbesa, Ogun State, where sandy soil is most commonly used for planting. A lot of farmers, especially in the rural communities of Igbesa, operate using the manual methods of irrigation, which results in water wastage and low farm produce yield. In light of this, this paper aims to design, implement and study the performance of an automated irrigation system for sandy soils in Igbesa, Ogun State. Sandy soil is a type of soil texture packed with lots of minerals that cannot retain moisture effectively due to its loose particles, and they are commonly found in various parts of southwestern Nigeria. This system uses an Arduino Uno R3 microcontroller with a resistive soil moisture sensor that detects the moisture changes in sandy soils and triggers a mini-DC motor pump when the moisture level of the sandy soil falls below a given threshold set in the software code in the Arduino IDE. Results indicate that effective irrigation scheduling helps the sandy soil retain moisture and the device operate effectively when the moisture readings detected by the resistive soil moisture sensor decrease within seconds of detection. The early adoption of an automated irrigation system by rural farmers in Igbesa will not only increase farm produce yields but also reduce the cost of hiring personnel to perform manual irrigation methods on farmlands.